Differential Analysis of Heart Rate, Facial Expressions and Brain Wave During Learning of Visual- and Text-Based Languages - Umezawa, Katsuyuki; Koshikawa, Takumi; Nakazawa, Makoto; Hirasawa, Shigeichi (2024 IEEE World Engineering Education Conference (EDUNINE), 2024)
From 2020, programming education has become compulsory in elementary schools. Visual-based programming languages are becoming popular as an introduction to programming. At universities, students learn text-based programming languages such as C and Java. Much research has been conducted on the transition from visual- to text-based programming languages. However, most related studies are limited to questionnaire evaluation after learning. In this study, we focus on evaluation during learning. Specifically, 18 types of biometric information (heart rate, 12 facial expressions, and 5 types of brain waves) of learners are measured during visual- and text-based programming language learning. According to the experimental results, the values of "sadness" and "brain wave representing difficulty" were higher when using a visual-based programming language than when using a text-based programming language. Furthermore, the difference was larger in the group with poor keyboard input skills. This group performed the task while feeling contempt, sadness, negative emotions, and difficulties.